Applied calculus for the managerial, life, and social sciences - Tan, S. T. (Thomson Brooks/Cole, 2005)
I have used this text in Applied Calculus I and Applied Calculus II for one academic year and part of another. I have looked at similar texts that are essentially of a traditional nature with some limited inclusion of technology. In that genre of texts, this book is, in my opinion, near the top of the heap. The exposition and development of topics is good. The book is sufficiently precise in defining the key concepts of calculus. The examples are clear and illustrative. From the perspective of a traditional, algebraic approach to the subject, this text is excellent, with a bevy of supporting exercises.